Remote Postdischarge Treatment of Patients With Acute Myocardial Infarction by Allied Health Care Practitioners vs Standard Care The IMMACULATE Randomized Clinical Trial - Chan, Mark Y (AMER MEDICAL ASSOC, 2021)
10.1001/jamacardio.2020.6721